Upaya Peningkatan Status Kesehatan Pada Bayi Di Masa Pandemi Covid-19 Melalui Imunisasi - Dhonna Anggreni; Ika Yuni Susanti; Dyah Siwi Hety (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2021)
Immunization is the most effective and efficient public health effort in preventing several dangerous diseases. The purpose of this activity is to increase the knowledge of mothers and health cadres about immunization during the Covid-19 pandemic. So that mothers still want to give complete immunizations to babies and are not afraid and anxious to come to the puskesmas to immunize their babies. In the end, the health status of babies can still be improved even though the Covid-19 pandemic is currently happening. This activity is carried out by providing education and training on all matters related to immunization during the Covid-19 pandemic. From the results of the evaluation of this activity, it was found that there had been an increase in knowledge of mothers and cadres about immunization during the pandemic period. The hope of this activity is that the immunization activity will continue without any hindrance, in which mothers still want to bring their babies to be immunized and feel safe and comfortable.